2010
DOI: 10.1021/bm1001125
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Enzyme Reactions in Multicompartment Microparticles

Abstract: Spherical biopolymer particles have been fabricated, applying coprecipitation with calcium carbonate, followed by cross-linking of the macromolecules and dissolution of the inorganic support. Particles made of roughly 80% horseradish peroxidase (HRP) as well as glucose oxidase (GOX) were prepared and enzyme activities were confirmed, applying the Amplex Red assay. The enzyme particles were reusable for at least six times, with a remaining activity of 30-50% from the initial one. When multiple coprecipitation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
127
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(133 citation statements)
references
References 37 publications
(64 reference statements)
1
127
0
2
Order By: Relevance
“…The inherent properties of hydrogels make the local PDT and local sustained-releasing chemotherapy possible, which can reduce the side effects of PDT and chemotherapy. Recently, several multifunctional multi-compartment systems, which can effectively encapsulate multiple drugs within the same matrix, have been designed by using different techniques, such as layer-by-layer assembly, emulsification, and so on [60,61]. However, it is a big challenge to construct elaborate drug delivery systems that combine chemotherapy and PDT at the action site [62,63].…”
Section: Combination Of Pdt and Chemotherapymentioning
confidence: 99%
“…The inherent properties of hydrogels make the local PDT and local sustained-releasing chemotherapy possible, which can reduce the side effects of PDT and chemotherapy. Recently, several multifunctional multi-compartment systems, which can effectively encapsulate multiple drugs within the same matrix, have been designed by using different techniques, such as layer-by-layer assembly, emulsification, and so on [60,61]. However, it is a big challenge to construct elaborate drug delivery systems that combine chemotherapy and PDT at the action site [62,63].…”
Section: Combination Of Pdt and Chemotherapymentioning
confidence: 99%
“…The inner capsules were modified by metal nanoparticles, and upon near-infrared laser illumination the inner part of such dualcapsules was released. Three coupled enzymes were encapsulated into concentric multi-compartment CaCO 3 particles via co-precipitation [105]. These enzymes were incorporated in separated compartments together with two spacing compartments made of bovine serum albumin (BSA).…”
Section: Multi-compartment Particles and Capsulesmentioning
confidence: 99%
“…A summary of developments in the area of enzymes was recently presented. In another study, a coupled chain reaction in multiple concentric CaCO 3 particles/capsule was investigated [103]. Research in the area of enzyme-catalyzed reactions revealed very promising approaches for treatment of diseases; there preserving catalytic activity of enzyme is one of the most significant factors [104].…”
Section: Multiple Stimuli Release and Multicompartment Structures-relmentioning
confidence: 99%